The Role of the Dark Triad and Materialistic Orientation in Evaluating an Ethically Unfounded Economic Decision - Milena V. Baleva; Dmitry S. Kornienko; Nadezhda P. Yachmeneva (RUDN Journal of Psychology and Pedagogics, 2023)
The authors consider the role of the Dark Triad traits in making an ethically unfounded economic decision caused by an artificial increase in prices against the background of forced consumer demand. They test hypotheses about the positive associations of dark traits with assessments of an ethically unfounded choice and the moderating (facilitating) role of materialistic orientation in the manifestation of these associations. It is assumed that the highest positive assessments of an unethical economic decision will be observed with a combination of high values in the dark traits and the materialistic orientation. The study involved 462 firstto fourth-year students aged 17 to 46 (M = 21.20; SD = 3.09), including 80 males (17.3%) and 382 females (82.7%). To diagnose moral choice in terms of economic behavior, the participants were asked to consider two situations, in each of which it was required to assess the degree of ethicality of financial decisions aimed at raising prices. In the first situation, this decision was justified, since it was aimed at compensating objective expenses, while, in the second situation, it was unjustified, since it had no objective economic prerequisites. The dark traits and materialistic orientation were measured by standardized questionnaires. The data were processed using correlation analysis (including partial correlations) and factorial ANOVA. It was found that, at high levels of the Dark Triad, there was a tendency to make ethically unfounded financial decisions, but the materialistic orientation did not increase this tendency. For the first time, it was revealed that the tendency to make ethically unjustified financial decisions manifests itself in a combination of high values of the Dark Triad (in particular, Machiavellianism) and low values of the materialistic orientation (in particular, the Acquisition centrality). Notably, that, for total indicators, this pattern can be traced only at the level of a statistical trend while, for Machiavellianism, it is at a statistically significant level. The results obtained indicate that the unethical economic decision of a ‘dark’ personality may be based on a non-utilitarian motivation, which manifests itself in the rejection of profit for the sake of the opportunity to cause harm.